Preliminary studies on the characteristics of coir twines - Gopalan Nayar, S (Indian Journal of Fisheries, 2016)
Coir in the form of twines and ropes is a fishing gear material widely used, particularly in South India, for the fabrication of essential components of several types of fishing implements. Very little information is on record elucidating the essential dynamic characteristics of this important gear material. Miyamoto and Shariff (1958) in an earlier communication have presented certain details on the characteristics and rotting qualities of one variety of coir twine. The present study on the characteristics of different grades of coir twines was undertaken at the instance of Dr. Miyamoto with a view to evaluate the qualities of the different grades of coir twines and to facilitate determination of their utility as a fishing gear material.